Persistence of insecticide residues in olives and olive oil - Cabras, P.; Angioni, A.; Garau, V. L.; Melis, M.; Pirisi, F. M.; Karim, M.; Minelli, E. V. (Amer Chemical Soc, 1997)
The decay rate of six insecticides (azinphos methyl, diazinon, dimethoate, methidathion, parathion methyl, and quinalphos) used to control Dacus oleae was studied. Degradation of pesticides showed pseudo-first-order kinetics with correlation coefficients ranging between -0.936 and -0.998 and half-lives between 4.3 days for dimethoate and 10.5 days for methidathion. Residues in olive oil were greater than on olives, with a maximum concentration factor of 7. Dimethoate was the only pesticide with lower residues in the oil than on the fruits. Olive washing affects pesticide residues ranging from no reduction to a 45% decrease. During 8 months of storage of the olive oil, diazinon, dimethoate, parathion methyl, and quinalphos did not show any remarkable difference, while methidathion and azinphos methyl showed a moderate decrease.
Keywords: residues; insecticides; olives; olive oil; storage; washing